Creation of Particular Learning Methods for Blind Children - Muzaffar kizi , Rakhmonnazarova Feruzakhon (International Journal on Human-Computing Studies, 2025)
The aim of the research is to discuss the process of creating teaching methods for visually impaired children, emphasizing the benefits of individualised instruction, accessible materials, and the integration of assistive technologies. By utilising these techniques, education can ensure equal opportunity for blind children to thrive socially and academically. In order to overcome some obstacles in education needs of children with visual impairments, it is essential to implement some methodologies like Braille which has always been the oldest and commonly used, audio books, tactile graphics. The results of using the Braille method, tactile learning, and auditory learning for blind children are generally positive and have been shown to contribute significant results to their overall development and foster their academic success, social development which lead to their future employment.